2018
DOI: 10.3390/technologies6020041
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Statistical Diagnosis to Determine the Probability of Survival in Adult Subjects with Traumatic Brain Injury

Abstract: Determining the probability of survival after injury is important as it can inform triage, clinical research and audit. A number of methods have been reported for determining the probability of survival after injury. However, these have shortcomings and thus further developments are needed to improve their reliability and accuracy. In this study, a Bayesian method called Predictive Statistical Diagnosis (PSD) was developed to determine probability of survival in 4124 adults (age: mean = 67.9 years, standard de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Table 6 provides the results for determining %Ps for cases included in the validation set. The results obtained using IRCC were compared to those from Ps14 (which were already available from the provided TARN database) and PSD (which were determined in an earlier study [26]). Ps14 uses a range of 0–100 to represent %Ps, with a value higher than 50 considered as a survivor, otherwise a not survivor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 6 provides the results for determining %Ps for cases included in the validation set. The results obtained using IRCC were compared to those from Ps14 (which were already available from the provided TARN database) and PSD (which were determined in an earlier study [26]). Ps14 uses a range of 0–100 to represent %Ps, with a value higher than 50 considered as a survivor, otherwise a not survivor.…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier study, we reported a method of determining Ps based on predictive statistical diagnosis (PSD) [26]. PSD's principle is based on Bayesian statistic which is a well‐establish method of data classification.…”
Section: Methods To Determine Psmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the capability of ML in extracting important features from large multidimensional data sets predicting real-life outcomes, it is often seen as having significant potential in the field of trauma when it comes to improving access and quality of care, across different regional trauma systems and within a local trauma environment [ 16 ]. Trauma incorporates numerous factors in many forms affecting different organs, and their consequence could be related to the individual’s physiological attributes (e.g., age, fragility, premedical conditions) [ 17 ]. These factors translate into substantial quantity of data features, leading to high dimensional data.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of the age with AIS and GCS significantly improved the PSD performance resulting in 82.4% and 65.2% correct identification for the survivors and not survivors respectively. The inclusion of systolic blood pressure with age, AIS and GCS resulted in 83.3% and 64.3% correct identification of survivors and not survivors respectively (Saleh et al, 2018). The study evaluated the performance of PSD in determining the probability of survival in adult subjects with TBI.…”
Section: Psd Modelmentioning
confidence: 99%